2003
DOI: 10.1097/01.tp.0000062574.18648.7c
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation from controlled non–heart-beating donors: an increased incidence of biliary complications

Abstract: Donor warm ischemic time may predispose hepatic allografts to an increased incidence of ischemic type strictures. Although graft and patient survival was similar to a cohort of HBD recipients, caution is urged with the use of these organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
228
6
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(250 citation statements)
references
References 22 publications
15
228
6
1
Order By: Relevance
“…The use of NHBD grafts has been previously shown to lead to a higher incidence of biliary complications. [19][20][21] A recent study from Johns Hopkins revealed the presence of biliary casts, proximal to ductal anastomotic strictures, in 35% of its NHBD liver transplants. 22 A possible reason that our current study did not show an increased incidence of BCS in NHBD grafts is the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NHBD grafts has been previously shown to lead to a higher incidence of biliary complications. [19][20][21] A recent study from Johns Hopkins revealed the presence of biliary casts, proximal to ductal anastomotic strictures, in 35% of its NHBD liver transplants. 22 A possible reason that our current study did not show an increased incidence of BCS in NHBD grafts is the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies the incidence is not increased (22,25). However, anastomotic complications might be obscured by a high number of diffuse NAS (26).…”
Section: Risk Factors For Anastomotic Complicationsmentioning
confidence: 99%
“…Complications in groups with WIT less than 30 min were similar, the incidence of liver graft dysfunction increased with the elongation of WIT and the incidence of biliary blockage was positively related to the survival time of recipient animals [22][23][24] .…”
Section: Relationship Between Wit and Complicationmentioning
confidence: 99%